Transitions Pop-ups: Co-designing client-centred support for disabled youth transitioning to adult life - Seko, Yukari; Oh, Anna; Thompson, Laura; Bowman, Laura R.; Curran, C. J. (Frontiers in Rehabilitation Sciences, 2024)
Background: When transitioning to adulthood, youth with disabilities and their families face many service gaps. Successful inter-agency collaborations can promote family-centred, inclusive transition support amenable to personal choice and health conditions. This paper reports the 3-year co-design process of an innovative transition service that links a pediatric hospital and adult service agencies and addresses key areas of transition preparedness with joint accountability. Methods: A team of pediatric rehabilitation professionals, adult service providers, young adults with disabilities and their families, and researchers engaged in a co-design process over three years. Following a design thinking (DT) framework, the team went through an iterative process of Emphasize, Define, Ideation, Prototyping, and Testing phases. The trial-and-error process allowed for deeper reflection and an opportunity to pivot the design. Results: The co-design yielded Transitions Pop-ups, a nimble service model that can ‘pop up’ at critical times and places to meet clients’ urgent and emergent transition-related needs. Two pilot sessions were conducted at the testing phase with adult service agencies. The final model included five key elements: 1) community partnership; 2) targeted information sharing; 3) peer mentoring; 4) action (on-the-spot completion of a key transition task/activity such as submitting an adult funding application); and 5) warm handover. Conclusion: The co-design process highlighted the importance of open communication and iterative prototype testing as a means for trialing new ideas and clarifying the intent of the project. The DT framework optimally facilitated the co-development of a contextually relevant and sustainable service model for pediatric rehabilitation clients and families.